Financial burden of medicines in five northern european countries: A decommodification perspective - Aaltonen, Katri (Elsevier, 2025)
Affordable access to healthcare including medicines is a key social policy goal in Europe. However, it has rarely been addressed in comparative social policy research. Although the concept of decommodification has already been used in the context of healthcare and sickness benefits, we argue that the scope of such studies should be expanded to medicines to understand how welfare states protect their citizens from market forces in case of illness. We examine and compare the relationship between income, other characteristics, and subjective financial burden of medicines (FBM) across five countries with universal health systems pursuing egalitarian aims (Denmark, Finland, the Netherlands, Norway and Sweden). Analyses using 2017 EU-SILC microdata and linear probability models showed large differences in the level of FBM across countries, with the highest income quintile in Finland reporting FBM more frequently than the lowest income quintile in Denmark. Finland differed from the rest by increasing probability of FBM with age. In other countries, middle-aged adults tended to be the most affected, and older adults were well-protected. The association between income and FBM was strongest in the Netherlands; however, the higher probability of FBM was skewed towards the lower quintiles in all countries. FBM and financial burden of medical care were strongly associated although FBM tended to be more common. Unmet needs for medical examination were rare and lacked sensitivity in capturing manifestations of market risk. Decommodification literature has focused healthcare services as proxy of access; nevertheless, our study shows that further functions, and broader outcomes should be examined to capture market risk. Our evidence further highlights that important differences can be found even in countries with relatively similar health policy aims. The cost of medicines should be considered in comparative studies of health and welfare states.